The role of Digital Leadership Capability and Intercultural Competences as mediation of Digital Transformation on MSME Business Performance - Chairunnisa, Fitri; Aira, Dian Mala Fithriani; Siregar, Ade Perdana (Dinasti International Journal of Digital Business Management, 2023)
Digital transformation is one of the business strategies for improving business performance and increasing competitiveness. Leaders in organizations who have digital capabilities can become innovation leaders in their organizations. Digital transformation is very much influenced by users, so the close relationship with human aspects and intercultural relations play a big role in this change. Strengthening the digital capabilities of leaders of MSME business organizations and equipping them with intercultural competence should improve business performance. The objectives of this research are (1) to analyze the influence of digital transformation on MSME business performance; (2) analyzing the influence of digital transformation on digital leadership capability; (3) analyzing the influence of digital transformation on intercultural competences; (4) analyzing the influence of digital leadership capability on MSME business performance; (5) analyzing the influence of intercultural competences on MSME business performance; (6) analyzing the role of digital leadership capability in mediating the influence of digital transformation on MSME business performance; (7) analyze the role of intercultural competences in mediating the influence of digital transformation on MSME business performance. The data analysis method used is Structural Equation Modeling (SEM) measurements using SmartPLS software. The research results can be concluded as follows: (1) digital transformation shows a significant positive influence on MSME business performance; (2) digital transformation shows a significant positive influence on digital leadership capability; (3) digital transformation shows a significant positive influence on intercultural competences; (4) digital leadership capability shows a significant positive influence on MSME business performance; (5) intercultural competences show a significant positive influence on MSME business performance; (5) digital leadership capability as a mediating influence of digital transformation shows a significant positive influence on MSME business performance; (6) intercultural competences as a mediating influence of digital transformation show a significant positive influence on MSME business performance